Impact of Mobile Application Characteristics on the Application Engagement and Intention for Continuing Use in Tourism Industry - İlkan, Şensev Payan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
Mobile devices have become essential components of the tourism industry. The importance of travel-based mobile apps is subsequently on the rise, particularly in marketing. Going onto mobile platforms is simple and necessary, even for the smallest businesses, as they will be able to connect with many travelers worldwide who prefer using their smartphones to plan their trips. In such a competitive environment, businesses should seek ways to attract consumers to their apps and keep them engaged. The study investigates the conceptual model using the Diffusion of Innovation Theory (DOI) and Uses and Gratifications Theory (UGT). An online survey questionnaire was designed and administered to 510 European consumers who were required to have a smartphone and use a mobile application for their tourism transactions. The study outcomes show that simplicity, compatibility, benefit, and playfulness positively influence user satisfaction, and perceived value is positively influenced by simplicity, compatibility, and benefit. The study also revealed that mApp engagement and intention for continuing use are positively impacted by user satisfaction. These outcomes will generally shed light on tourism organizations, software mobile application developing companies, and user interface/user experience designers regarding the consumer’s perception and requirements from a mobile application.

ÖZ: Mobil cihazlar turizm endüstrisinin önemli bileşenlerinden birisi olarak görülmektedir. Seyahat tabanlı mobil uygulamaların önemi turizmde gün geçtikçe, özellikle pazarlama açısından, artmaktadır. Seyahatlerini planlamak için akıllı telefonlarını kullanmayı tercih eden dünya çapındaki birçok gezginle bağlantı kurabileceklerinden, mobil platforma geçmek en küçük işletmelerin bile katılması için bir gereksinimdir. Böylesine rekabetçi bir ortamda işletmeler, tüketicileri uygulamalarına çekmenin ve ilgilerini canlı tutmanın yollarını aramalıdırlar. Bu çalışma İnovasyonun Yayılması Teorisi (Diffusion of Innovation Theory -DOI) ile Kullanımlar ve Doyumlar Teorisini (Uses and Gratifications Theory -UGT) kullanılarak kavramsal modeli araştırmaktadır. Çevrimiçi anket formu tasarlanmış olup, her türlü turizm işlemleri için akıllı telefon ve mobil uygulama kullanan 510 Avrupalı tüketiciye uygulanmıştır. Çalışma sonuçları, sadelik, uyumluluk ve faydanın kullanıcı memnuniyeti ve algılanan değer üzerinde olumlu bir etkiye sahip olduğunu, oysa yalnızca eğlencenin kullanıcı memnuniyeti üzerinde olumlu bir etkiye sahip olduğunu göstermektedir. Çalışma ayrıca, mobil uygulama etkileşimi ve sürekli kullanım niyetinin kullanıcı memnuniyetinden olumlu etkilendiğini ortaya koydu. Bu sonuçlar genel olarak turizm organizasyonlarına, mobil yazılım uygulama geliştiren firmalara ve kullanıcı arayüzü/kullanıcı deneyimi tasarımcılarına tüketicinin mobil uygulamadan algısı ve gereksinimleri konusunda ışık tutacaktır. Anahtar Kelimeler: Mobil Turizm Uygulaması
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2023. Co-Supervisor: Prof. Dr. Turgay Avcı and Supervisor: Prof. Dr. Ali Öztüren.
Keywords: Tourism Faculty; Tourism--Smart Tourism--Mobile Applications; Tourism--Information and Communication technology--Innovative Tools--Tourism; Tourists--Smart Tourism Technology--Smart Destinations; Mobile Tourism Application, Diffusion of Innovation Theory, Uses and Gratifications Theory, Perceived Value, User Satisfaction, Mobile Application Engagement, Intention to Continue Use; Tourism, Social networks, Application service providers, Information systems, Smartphones; Smart tourism, recommendation system, multi agent system, web-based